Carbon fabric based solar steam generation for waste water treatment - Higgins, M. W.; Rahmaan, Shakeel A. R.; Devarapalli, Rami Reddy; Shelke, Manjusha V.; Jha, Neetu (Solar Energy, 2018)
Decontamination of waste water is one of the most practical techniques to tackle the worldwide clean water shortage. In recent times, solar steam based decontamination of contaminated water has been attested as a potential sustainable strategy to get clean water using renewable resources. Herein, we report the utilization of Carbon fabric and Titanium Nanorods on Carbon Fabric for solar steam based water purification techniques. The performance of Carbon Fabric was tested under different conditions and the results proved that Carbon Fabric has excellent light to heat conversion capabilities in both real and ideal conditions. Owing to the excellent performance of Carbon Fabric, it was used for purification of different types of contaminated water. About 99.9% of salt and 87% of organic contaminants were removed from saline water and organic waste water respectively, using a simple low cost carbon fabric based homemade prototype. We also present the application of Titanium Nanorods on carbon fabric for the efficient removal of dye molecules like Rhodamine B from contaminated water using solar driven interfacial steam generation mechanism.
Keywords: Desalination; Dye degradation; Solar steam; Waste water treatment